Cardiac rehabilitation after acute myocardial infarction in Sweden – evaluation of programme characteristics and adherence to European guidelines: The Perfect Cardiac Rehabilitation (Perfect-CR) study. (29th August 2020) - Ögmundsdottir Michelsen, Halldora; Sjölin, Ingela; Schlyter, Mona; Hagström, Emil; Kiessling, Anna; Henriksson, Peter; Held, Claes; Hag, Emma; Nilsson, Lennart; Bäck, Maria; Schiopu, Alexandru; Zaman, M Justin; et al.
Abstract: Background: While patient performance after participating in cardiac rehabilitation programmes after acute myocardial infarction is regularly reported through registry and survey data, information on cardiac rehabilitation programme characteristics is less well described. Aim: The aim of this study was to evaluate Swedish cardiac rehabilitation programme characteristics and adherence to European Guidelines on Cardiovascular Disease Prevention. Method: Cardiac rehabilitation programme characteristics at all 78 cardiac rehabilitation centres in Sweden in 2016 were surveyed using a web-based questionnaire (100% response rate). The questions were based on core components of cardiac rehabilitation as recommended by European Guidelines. Results: There was a wide variation in programme duration (2–14 months). All programmes reported offering an individual post-discharge visit with a nurse, and 90% ( n = 70) did so within three weeks from discharge. Most programmes offered centre-based exercise training ( n = 76, 97%) and group educational sessions ( n = 61, 78%). All programmes reported to the national audit, SWEDEHEART, and 60% ( n = 47) reported that performance was regularly assessed using audit data, to improve quality of care. Ninety-six per cent ( n = 75) had a core team consisting of a cardiologist, a physiotherapist and a nurse and 76% ( n = 59) reported having a medical director. Having other allied healthcare professionals included in the cardiac rehabilitation team varied. Forty per cent ( n = 31) reported having regular team meetings where nurses, physiotherapists and cardiologist could discuss patient cases. Conclusion: The overall quality of cardiac rehabilitation programmes provided in Sweden is high. Still, there are several areas of potential improvement. Monitoring programme characteristics as well as patient outcomes might improve programme quality and patient outcomes both at a local and a national level.